Mercury methylation rates in Deception Island (Maritime Antarctica) waters and pyroclastic gravel impacted by volcanic mercury. (March 2021) - Bento, Beatriz; Hintelmann, Holger; dos Santos, Margarida Correia; Cesário, Rute; Canário, João
Abstract: Deception Island is an active volcano in the Antarctica being volcanism a source of mercury. To improve the understanding of the Hg cycle in this remote ecosystem, pyroclastic gravel and water samples were collected and total (THg) and monomethylmercury (MMHg) concentrations were measured as well as the potential for Hg methylation. Gravel samples collected close to active fumaroles showed the highest THg levels (72 ng/g) while in water samples the highest concentrations of THg (1.2 ng/L) and MMHg (0.45 ng/L) where found. Methylation activity was barely observable in gravel samples. Biotic methylation rates in water were up to 13 times higher compared to those recorded previously in other polar waters. Abiotic methylation processes also play an important role, with up to 0.54 ± 0.43% of added Hg converted instantaneously to MMHg. These results suggest that Deception Island presents favourable conditions for MMHg explaining the elevated concentrations of both THg and MMHg in this ecosystem. Highlights: Deception Island (DI) is an active volcano in the South Shetland Archipelago. Active volcanism in DI is the main source of Hg in DI. Hg methylation rates in DI waters are higher than in other polar aquatic systems. Methylmercury proportions (THg) are up to 450% higher than other marine systems. DI is a natural Hg contaminated system with direct impacts on living organisms.